Neurosains dalam Pendidikan Anak Usia Dini - Asri Fernianti (SITASI: Journal of Islamic Studies and Inclusive Education, 2026)
This study aims to analyze the application of neuroscience principles in early childhood as a basis for developing effective and holistic learning strategies. This research employs a literature review (library research) method by examining various scientific literatures related to child brain development, cognitive stimulation, and neuroscience-based learning approaches in the context of early childhood education. The results show that the application of neuroscience principles, such as the importance of environmental stimulation rich in positive experiences, emotional engagement in the learning process, and respect for the uniqueness of each child's brain, contributes significantly to optimizing children's learning potential. Neuroscience-based learning strategies encourage teachers to create activities that stimulate various areas of the brain through play, sensory exploration, and meaningful creative activities. Thus, an understanding of neuroscience can serve as an important foundation for early childhood educators in designing adaptive, enjoyable, and developmentally appropriate learning experiences.